2022
DOI: 10.1186/s12905-022-01790-2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of the relationship of female genital mutilation with birth outcomes in Somalia

Abstract: Background Female genital mutilation (FGM) is defined as the partial or complete removal of the external female genitalia for non-medical reasons. There are some complications related to childbirth that concern both the mother and the baby. In this study, we aimed to evaluate the birth outcomes of FGM, which is widely applied in Somalia. Methods The study included 268 women who gave birth at 37–42 weeks of gestation with a cephalic singleton, 134 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, no information is available in the literature about the current prevalence and types of FGM in Somalia. 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no information is available in the literature about the current prevalence and types of FGM in Somalia. 5 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from Somalia, Kulaksiz et al 5 showed that FGM leads to prolongation of the second stage of labor, increased risk of perineal tear, increased need for emergency cesarean section, and increased neonatal ICU need in infants.…”
Section: Introductionmentioning
confidence: 99%